Brain microvascular endothelial cells possess a second cilium that arises from the daughter centriole - Thirugnanam, Karthikeyan; Gupta, Ankan; Nunez, Francisco; Prabhudesai, Shubhangi; Pan, Amy Y.; Nauli, Surya M.; Ramchandran, Ramani (Frontiers in Molecular Biosciences, 2023)
Primary cilia from the brain microvascular endothelial cells (ECs) are specialized cell-surface organelles involved in mediating sensory perception, cell signaling, and vascular stability. Immunofluorescence (IF) analysis of human primary brain microvascular ECs reveals two cilia per cell. To confirm the in vitro observation of the 2-cilia phenotype in human primary brain ECs, ECs isolated from mouse brain were cultured and stained for cilium. Indeed, brain ECs from a ciliopathic mouse (polycystic kidney disease or Pkd2 -/-) also possess more than one cilium. Primary cilium emerges from the mother centriole. Centriole analysis by IF suggests that in brain ECs, markers for mother and daughter centrioles stain both cilia suggesting that the second cilium in brain ECs arises from the daughter centriole. Further quantification of cilia size in brain ECs revealed that cilia arising from the mother centriole are bigger in size compared to cilia from the daughter centriole. Cell cycle analyses by immunoblotting and flow cytometry suggest that ciliary proteins ARL13B and IFT88 involved in brain EC ciliogenesis are highly expressed only in the G0/G1 and S phases of the cell cycle. The IF analyses of cells arrested at different cell cycle stages indicate that the 2-cilia phenotype is highly specific to G0/G1 phase. Our findings suggest that in addition to mother centriole, daughter centriole also plays a role in ciliogenesis in primary cultured ECs.Proteins were isolated from HBMECs using RIPA buffer (Sigma Cat#R2078) with a complete mini EDTAfree protease inhibitor cocktail (Roche Cat#11836170001) and PhosSTOP phosphatase inhibitor (Roche